2017
DOI: 10.3892/or.2017.5479
|View full text |Cite
|
Sign up to set email alerts
|

Cancer-associated fibroblasts enhance pancreatic cancer cell invasion by remodeling the metabolic conversion mechanism

Abstract: We investigated the mechanism of cancer-associated fibroblasts (CAFs) in promoting the invasion and metastasis of pancreatic cancer cells in a non-vascular manner. We verified the original generation of isolated cultured CAFs and normal fibroblasts (NFs) based on the expression of α-SMA and vimentin, and we examined the cell glycolysis level through glucose consumption and lactate production experiments. The mRNA and protein expression of CAF glycolytic enzymes, lactate dehydrogenase and pyruvate kinase m2, we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
79
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 96 publications
(79 citation statements)
references
References 31 publications
(34 reference statements)
0
79
0
Order By: Relevance
“…Tumor cells transmit signals to force the stromal cells to undergo aerobic glycolysis and produce more metabolites. In turn, tumor cells absorb the metabolites to fight against nutrient withdrawal and satisfy their anabolic requests to match the high proliferation rate (21, 44).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Tumor cells transmit signals to force the stromal cells to undergo aerobic glycolysis and produce more metabolites. In turn, tumor cells absorb the metabolites to fight against nutrient withdrawal and satisfy their anabolic requests to match the high proliferation rate (21, 44).…”
Section: Discussionmentioning
confidence: 99%
“…In most tissues and tumors, circulating lactate is a major source of tricarboxylic acid (TCA) intermediates, and the contribution of glucose to the TCA cycle is mostly through circulating lactate (19). Based on the reverse Warburg effect, stromal cells act as excellent energy suppliers under harsh environmental conditions (20,21).…”
mentioning
confidence: 99%
“…In the TME of various tumors, humoral factors released from CAF play fundamental roles in tumor metastasis, resistance to chemotherapy, and epithelial-to-mesenchymal transition (EMT). [15][16][17][18][19][20] In malignant lymphoma, we have previously reported that a mouse-derived fibroblastic reticular cell (FRC) line supported lymphoma cells from patient-derived xenograft (PDX) models, indicating that fibroblasts also play many functional roles in the lymphoma microenvironment. 21,22 This report examined how CAF isolated from primary lymphoma samples support primary lymphoma cells in vitro and clarified the components vital for these abilities.…”
Section: Introductionmentioning
confidence: 99%
“…Pancreatic stellate cells are a subset of CAFs . CAFs are a major component of pancreatic cancer stroma, derived from different kinds of progenitor cells such as fibroblasts, pancreatic stellate cells, and epithelial, endothelial, and mesenchymal stem cells . CAFs express α‐smooth muscle actin (α‐SMA), a well‐known and reliable marker of CAF, stromal cell‐derived factor‐1α, fibroblast activation protein, and fibroblast specific protein‐1 .…”
Section: Role Of Desmoplastic Stroma In the Development Of Pancreaticmentioning
confidence: 99%